Strategi Pemasaran Menggunakan Iklan Digital Marketing Berbasis SEO (Search Engine Optimization) - Santoso, Agung; Panglipursari, Dwi Lesno; Fikri, Abu Amar (IQTISHADequity jurnal MANAJEMEN, 2024)
Digital marketing advertising is a form of marketing that a company or brand uses to promote products using digital media or the internet. It aims to provide information and influence the public to buy and use its products. One of the digital marketing techniques used is SEO. SEO preparation is the first step before conducting an SEO process. It involves preparing the rules for using keywords used from both online ads, social media, and external links on each media. So when visitors want to search for information, they type keywords into Google. The SEO process will work according to the rules consisting of title, description and tags then it will be directly optimized. Optimization is divided into 2, namely on-page optimization, namely how to optimize content to increase visibility and improve performance on a website page. Off-page optimization is a way to optimize a website and improve performance from outside the website page